The Relationship Of Diet And Physical Activity With The Incidence Of Hypertension In The Community In Tenga Village - Theresia Desy Sumarna; Achmad Paturusi; Agusteivie Tellew; Alva Supit; Lucyana Pongoh; Theo Mautang (International Journal of Health Engineering and Technology, 2026)
Hypertension is a non-communicable disease that is one of the main health problems in South Minahasa Regency. Unhealthy diet and lack of physical activity are risk factors that can increase the incidence of hypertension in the community. This study aims to determine the relationship between diet and physical activity and the incidence of hypertension in the community in Tenga Village. This study uses a quantitative method with a Cross-Sectional design. The research sample amounted to 120 respondents who were people who had conducted examinations at the Tenga Health Center. Data was collected using the Food Frequency Questionnaire (FFQ) questionnaire for diet and the Global Physical Activity Questionnaire (GPAQ) for physical activity, as well as blood pressure data from the Health Center. Data analysis used Chi-Square test and multivariate analysis. The results showed that the majority of respondents were female as many as 92 people (76.7%) and ≥50 years old as many as 83 people (69.2%). A total of 99 respondents (82.5%) had hypertension, 96 respondents (80.0%) had a hypertension-triggering diet, and 97 respondents (80.8%) had mild physical activity. The results of the Chi-Square test showed that there was a significant relationship between diet and the incidence of hypertension with a value of p=0.022 and there was a significant relationship between physical activity and the incidence of hypertension with a value of p=0.034. However, the results of the multivariate analysis showed that diet (p=0.118) and physical activity (p=0.162) did not have a significant relationship simultaneously with the incidence of hypertension. The conclusion of this study shows that there is a relationship between diet and physical activity and the incidence of hypertension in the community in Tenga Village based on bivariate analysis. Therefore, the community is expected to maintain a healthy diet and increase physical activity as an effort to prevent and control hypertension.